2019
DOI: 10.1101/mcs.a003988
|View full text |Cite
|
Sign up to set email alerts
|

A novel PAK3 pathogenic variant identified in two siblings from a Japanese family with X-linked intellectual disability: case report and review of the literature

Abstract: Intellectual disability (ID) is a clinically and genetically heterogeneous developmental brain disorder. The present study describes two male siblings, aged 7 and 1 yr old, with severe ID, spastic quadriplegia, nystagmus, and brain atrophy with acquired microcephaly. We used the exome sequencing to identify the causative gene in the patients and identified a hemizygous missense variant, c.1282T>A (p.W428R), in the p21-activated serine/threonine kinase 3 gene (PAK3), which is associated with X-linked ID. p.W428… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Our patient, similar to others with a PAK3 mutation, had no history of seizures; however, other families had members with epilepsy, which shows the clinical heterogeneity of PAK3 mutations [ 6 8 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our patient, similar to others with a PAK3 mutation, had no history of seizures; however, other families had members with epilepsy, which shows the clinical heterogeneity of PAK3 mutations [ 6 8 ].…”
Section: Discussionsupporting
confidence: 81%
“…The patient had features similar to those reported for other families carrying a PAK3 mutation, and comparisons are made in Table 1 [ 6 8 ]. A previous study reporting a multiplex pedigree family with a point mutation in PAK3 suggested that PAK signaling may be critical for neuronal connections underlying human cognitive function [ 4 ].…”
Section: Discussionmentioning
confidence: 57%
“…Twelve of them were located in the KD, and two were in the PBD/AID. Currently, only 1 deletion in exon 6-18 has been reported, which covers the major area of the PBD/AID and all of the KD [2,[8][9][10][11][12][13][14][15][16][17][18][19][20] (Table 2, Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…PAK3 mutations in humans are responsible for ID, developmental delay including motor and speech deficits, behavioral problems linked to increased aggression and violence, and severe epilepsy (Allen et al, 1998; Horvath et al, 2018; Iida et al, 2019; Magini et al, 2014; Rejeb et al, 2008). Behavior abnormalities belonging to the autistic spectrum, aggression, schizophreniform psychosis have been reported in patients with PAK3 mutations (Horvath et al, 2018; Qian et al, 2020).…”
Section: Discussionmentioning
confidence: 99%